Christelike hoëronderwysinstellings in Suid-Afrika: 'n Dokumentanalise - Diedericks, Morné; Wolhuter, Charl (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
This article examines the state of Christian higher education in South Africa, specifically focusing on institutions offering programs outside the field of Theology. The research question aims to identify trends and challenges within this context. The article analyses data from 2009 to 2022 and identifies a significant growth in Christian higher education institutions, especially within the private sector. However, the growth is not as pronounced as that of secular institutions. A closer look at Christian institutions reveals a decrease in institutions within the Philosophy, Religion, and Theology group, whereas, in contrast, there is a notable increase in Business, Economics, Management Studies and Education. Furthermore, it is noteworthy that Afrikaans-Christian higher education institutions have grown substantially from 2009 to 2022. The emerging Christian institutions, especially within the private sector, present potential opportunities for further growth and development within Christian higher education in South Africa. The data was analyzed based on the type of institutions (for-profit, non-profit, provisionally or fully registered), their faith orientation (secular, Christian, or Islamic), and the types of qualifications they offer. Program classification was further refined using the Classification of Educational Subject Matter (CESM) framework. Special attention was given to Christian higher education institutions (CHIs) offering programs outside of Philosophy, Religion, and Theology (CESM 17). The results indicate significant growth in Christian institutions within the private sector, particularly in Business, Economics, and Management Studies as well as Education, while a decline in traditional Theological programs was observed. Afrikaans-Christian institutions have also shown considerable growth. These emerging institutions present potential for further development in Christian higher education in South Africa.